A proposed syllabus for a modern mathematics content course for teacher training schools of Indonesia - Simanungkalit, Alfred 1938- ([Quezon City s.n.], 1971)
A syllabus for a modern mathematics content course for training elementary school teachers in Indonesia was constructed in this investigation. The investigator undertook documentary analysis of books, periodicals, annual reports, and unpublished materials used by the Bureau of Public Schools.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Mathematics -- Study and teaching (Elementrary) -- Philippines; Mathematics -- Study and teaching (Elementary) -- Indonesia